Effect of Phenylbutazone Administration on Insulin Sensitivity in Horses With Insulin Dysregulation - Kate L. Kemp; Nicholas K. Y. Yuen; Jazmine E. Skinner; François‐René Bertin (Journal of Veterinary Internal Medicine)
ABSTRACT Background Phenylbutazone is prescribed to manage pain caused by hyperinsulinemia‐associated laminitis. Phenylbutazone reduces glucose and insulin concentrations in horses with insulin dysregulation (ID) but the underlying mechanism of action is unknown. Hypothesis/Objectives Investigate the effect of phenylbutazone on tissue insulin sensitivity in horses. It is hypothesized that the reduced glucose and insulin concentrations in horses with ID receiving phenylbutazone are mediated by a higher tissue insulin sensitivity. Animals Fifteen light breed horses, including seven with ID. Methods Randomized cross‐over study. Horses underwent a modified frequently sampled intravenous glucose tolerance test (mFSIGTT) after 8 days of treatment with phenylbutazone (4.4 mg/kg IV daily) or placebo (5 mL 0.9% saline IV daily). After a 10‐day washout period, horses received the alternative treatment for 8 days and a second mFSIGTT. Minimal model analysis was performed, and the effects of ID status and phenylbutazone were investigated with p < 0.05 considered significant. Results In horses with ID, phenylbutazone increased tissue insulin sensitivity index (median [interquartile range]: 0.39 [0.14–0.74] vs. 0.56 [0.55–1.18] ×10−4 L/mIU/min, p = 0.03), and decreased glucose (21 726 [19 040–24 948] vs. 22 909 [22 496–26 166] mg/dL × min, p = 0.02) and insulin (19 595 [16 147—29 698] vs. 22 752 [20 578—31 826] μIU/mL × min, p = 0.03) areas under the curves. No effect was detected in horses administered placebo. Conclusion and Clinical Importance Phenylbutazone reduces insulin concentration in horses with ID by modulating tissue insulin sensitivity, suggesting that its relevance in the management of ID can extend beyond laminitis‐associated pain.